Observing Robot Touch in Context: How Does Touch and Attitude Affect Perceptions of a Robot's Social Qualities? - Arnold, Thomas; Scheutz, Matthias (2018 13th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2018)
The complex role of touch is an increasingly appreciated horizon for HRI research. The explicit and implicit registers of touch, both human-to-robot and robot-to-human, have opened up pressing questions in design and HRI ethics about embodiment, communication, care, and human affection. In this paper we present results of an MTurk survey about robot-initiated touch in a social context. We examine how a positive or negative attitude from the robot, as well as whether the robot touches an interactant, affects how a robot is judged as a worker and teammate. Our findings confirm previous empirical support for the idea of touch as enhancing social appraisals of a robot, though the extent of that positive tactile role was complicated and tempered by the survey responses» gender effects.